Cortical myoclonus and cerebellar pathology. - Tijssen, M; Thom, M; Ellison, D; Wilkins, P; Barnes, D; Thompson, P; Brown, P (2000)
OBJECTIVE: To study the electrophysiologic and pathologic findings in three patients with cortical myoclonus. In two patients the myoclonic ataxic syndrome was associated with proven celiac disease. BACKGROUND: The pathologic findings in conditions associated with cortical myoclonus commonly involve the cerebellar system, but there has only been one report of cerebellar pathology in a patient in whom cortical myoclonus was physiologically characterized antemortem. METHODS: Cortical somatosensory evoked potentials (SEPs) were recorded and EEG activity was averaged preceding myoclonic electromyographic activity. In one patient cortico-cortical inhibition was tested using two paired ipsilateral magnetic stimuli over the motor strip. Neuropathologic examination was carried out, including linear Purkinje cell densities/millimeter calculations for different regions of the cerebellum. RESULTS: The electrophysiology showed evidence of dysfunction of the sensorimotor cortex with enlarged SEPs and a time-locked cortical potential preceding the action myoclonus. In addition, motor cortical inhibition was abnormal in one case. Pathology showed unremarkable primary sensory, motor, and premotor cerebral cortices, except for unilateral gliosis of the motor cortex in one case. The cerebellum showed patchy atrophy and ongoing degeneration. A striking feature was the greater severity of Purkinje cell loss and Bergmann gliosis in the outer aspects than in the depths of the folia. CONCLUSIONS: Pathologic abnormalities are paradoxically mainly located in the cerebellum in some patients with cortical myoclonus, despite clear electrophysiologic evidence of cortical dysfunction. This observation suggests that enhanced excitability of the sensorimotor cortex may arise as a distant effect of cerebellar pathology.